G216(P) The Treatment Room on Children's Ward – A Quality Improvement Project. (7th April 2014) - Peng, M; Lovett, S; Damda, F
Abstract : Introduction: The Children's Ward at University Hospital Lewisham is a 16 bed inpatient unit serving the South London boroughs of Lewisham and Greenwich. The general paediatrics team working in this department is made up of 2 F1 trainees, 6 SHOs and 8 Paediatric Registrars. Minor procedures undertaken by the team take place daily in the treatment room on Children's Ward, such as peripheral cannula insertion, venepuncture, lumbar puncture, wound care and dressing changes. Aims: A quality improvement project was undertaken to enhance the design and organisation of the room in order to improve the efficiency and care given to all inpatients undergoing a minor procedure on the Children's Ward. Methods: An initial questionnaire was distributed amongst the junior paediatrics team to collect opinions on the state of the treatment room as it was then and explore ways of further improving it. After compiling a list of problems and suggestions to resolve these issues, a proposal was brought forward to the Departmental Matron and a small budget was allocated to implementing subsequent changes to the room. The same questionnaire was then re-distributed amongst the team to follow-up on the changes and discovers what difference, if any, these had made. Results: All 16 members of the junior paediatrics team disagreed or strongly disagreed that the treatment room was easy to use, stocked adequately or well-organised. The main problems highlighted were that it was untidy, there was limited labelling of drawers, the arrangement of equipment was not in a logical way and it was inadequately stocked. A new trolley of drawers was purchased, the layout of apparatus was rearranged, weekly stocking of equipment was designated to a named healthcare assistant and bright new labels were made. Subsequently, colleague satisfaction much improved. Conclusion: Improvement in the efficiency and care given to inpatients undergoing a minor procedure on the ward can be made by rearranging and restructuring a treatment room with very little resources required. By listening to the opinions of the junior paediatrics team who predominantly use the room and acting upon those ideas, small changes can make a large difference to daily routine procedures that are undertaken on a ward.